Russian Miter of Jerusalem Patriarchs (17th Century) - Chesnokova, Nadezhda P. (Actual Problems of Theory and History of Art, 2019)
The archival records of the Posolsky prikaz (Ambassadorial office) in the Russian State Archiveof Ancient Acts (RSAAA) contain evidence for the intensive contacts between the Jerusalem patriarchand the Russian government in the first part of the 17th century. The file on the Moscow visit of the Jerusalem patriarch’s envoy, Archimandrite Anthimos, in 1643 has been preserved with unique completeness.This provides new details on the works included in the order: the list of icons and materials used, the names of icon-painters and silversmiths, information about the organization of the artistic process as a whole and, finally, the cost of the materials and works executed. The miter of the Jerusalem patriarchs was made four years after a similar item was created in the Kremlin’s workshops in 1640 for the archbishopof Sinai. After leaving Moscow, the miter was altered in a way. It remains nowadays in the Monastery of Saint Catherine at Mount Sinai. Originally, the lower diadem of the Sinai miter was ornamented with fur. Moreover, there was no cross on the upper round patterned plate. The gem stones were added during the alteration. While decorating the miter, the Moscow masters had used pearls only. The sources say the Sinai miter was just a reproduction of an existing exemplar created earlier by court masters. The Jerusalem patriarch’s headdress was based on the same sample. Thus, we can imagine how the Jerusalem miter looked before its alteration, although there were some differences between it and the Sinai example. As we have already mentioned, the top of the Sinai miter was decorated with pearls, not gem stones, unlike the patriarchal headdress.